A New Solar Technology Technique for Wastewater and Seawater Treatment - El-Hadad, Omar; Siti Nuda Shafinie, Abdul Aziz (2014)
With the increasing water shortage in different parts of South-East Asia, like Singapore, and some parts of Indonesia and recently in Selangor, the need arises for more advanced technologies to treat wastewater to a level of purity where is can be used as potable. In this paper some improvements to an already available technique (the solar still) are introduced, in order to increase its productivity and make it more suitable to be used industrially, for large scale wastewater treatment projects. Problems facing the solar still are mainly related to the very low evaporation rate which is caused by the low effect of solar evaporation. Here we see a new idea to solve this problem, and introduce a low-cost application to treat wastewater, by trying to redesign the whole process under different parameters. Improvements introduced in this paper can also be used for seawater desalination.